How Concepts Travel in Actual Spaces: The Interdisciplinary Classroom as a Behavior Setting - Kalis, Annemarie (Journal of Interdisciplinary Studies in Education, 2023)
In interdisciplinary education, students find out that even basic concepts such as time, freedom or control mean different things for different disciplines and individuals. Through such encounters, students develop an ever-richer conceptual toolbox for making sense of the world. But, how do concepts travel (Bal, 2002) in an interdisciplinary classroom? I address this question from the perspective of behavior settings theory, which shows how the concrete spatiotemporal characteristics of an environment structure and guide the behavior of its participants. By means of a case study, I analyze the interdisciplinary classroom as a behavior setting and argue that concepts can travel when the setting stimulates students and teachers to spend time and interact with each other in specific ways.